TANEAN LANJANG SEBAGAI STRATEGI DAKWAH ANTISIPASI KONFLIK DALAM MASYARAKAT - Majid, Achmad Nurholis (al-Balagh : Jurnal Dakwah dan Komunikasi, 2017)
Tanean Lanjang is a very unique culture. Itâ€™sÂ from building construction, social interactions, and until the related spiritual values. This is reinforced by the daâ€™wahÂ strategy by theÂ theologian whoÂ are accepted by everyone who runs the culture. This research aims to describe the daâ€™wahÂ strategy of theologian in Tanean Lanjang culture. With qualitative descriptive method,Â this research found that strategy of daâ€™wah for encounteringÂ conflict conducted by theologian in Tanean Lanjang is Persuasive strategy, Al-Hikmah, Al-Mau’idzoh Hasanah. These methods are implemented within the Tanean Lanjang cultural community toÂ motivative, facilitative, and mediative objectives.